Pengaruh Konten Instagram Terhadap Kepuasan Followers @barkas.jogjakarta (International Forum of Researchers and Lecturers, 2023)
Digital media is growing rapidly in modern times like today, including the development of social media such as Instagram which is now popular social media. Marked by an increase in active users of Instagram social media every year in Indonesia, it creates new opportunities such as the Instagram account @barkas.jogjakarta. Until now the Instagram account @barkas.jogjakarta has 210.000 followers and 64.300 uploads. The @barkas.jogjakarta account is an account that provides the first and largest service for uploading used goods in Yogyakarta. This study aims to determine and analyze the effect of Instagram @barkas.jogjakarta content on followers' satisfaction. This study uses the Uses and Gratifications theory where social media users actively seek media that can meet their needs and get satisfaction. This study uses a quantitative approach by distributing questionnaires online. The population used in this study were Instagram followers @barkas.jogjakarta and obtained a sample of 100 respondents. The data testing technique in this study was assisted by using SPSS software version 27. The results of this study and also the variable Y (Followers Satisfaction). It is also strengthened by the results of the hypothesis test that there is an influence on Instagram @barkas.jogjakarta content on followers' satisfaction. The results of the coefficient of determination show that 51.6% of followers' satisfaction is influenced by Instagram content and the rest is influenced by other factors. Keywords: Content, Instagram, Satisfaction, Uses and Gratification.